PENGARUH LOCUS OF CONTROL, SELF ESTEEM, EQUITY SENSITIVITY AUDITOR INTERNAL TERHADAP KUALITAS AUDIT DENGAN GENDER SEBAGAI VARIABEL MEDIASI - Poluan, Margie Christanty; Sondakh, Jullie J.; Karamoy, Herman (Universitas Sam Ratulangi, 2016)
The objective of this research is to find out the influence of locus of control, self esteem, and equity sensitivity of the internal auditor on auditing quality with gender as mediating variable at Inspectorate Division of North Sulawesi Province. The respondents are all the 64 internal auditors of North Sulawesi Province. Inferential statistic has been applied to test the hypothesis specifically the Structural Equation Model with Partial Least Square Analysis (SEM-PLS), while for testing mediating; Variance Accounted for (VAF) has been applied. The results show that Locus of Control, Self Esteem and Self Esteem are all influencing factors on auditing quality, but not gender. Thus, gender cannot mediate the three factors for auditing quality. It is recommended that government auditors to maintain their Locus of Control and emotional quotient to avoid deviation from their rules of conduct for qualified auditing. It also helps increase public trust on the internal auditor of the government as transparent and accountable. They also need to keep their self esteem and equity sensitivity high, maintain gender equality as part of the commitment and solidity in conducting their tasks as auditors. Keywords: locus of control, self esteem, equity sensitivity, auditing quality, gender.